Simulation tool for active learning of introductory computer network subjects - Wan Mohd Ghazali, Khadijah; Hassan, Rosilah; Md. Ali, Zulkarnain (2011)
Abstract— Simulation software helps a learner of networking subject to have an active learning experience. There are many simulator tools available either freely or off the shelf. Hence, simulation tools need to be carefully chosen to maximize the benefit to the learners. In order to choose simulation tools, comparison is made from a number of simulation tools that are easily available for the public. The comparison made to the tools produce a recommendation of which tool is to be chosen in different study environments.